Coping with arid environments: A critical threshold for human expansion in Europe at the Marine Isotope Stage 12/11 transition? The case of the Iberian Peninsula. Issue 153 (April 2021) - Blain, Hugues-Alexandre; Fagoaga, Ana; Ruiz-Sánchez, Francisco Javier; García-Medrano, Paula; Ollé, Andreu; Jiménez-Arenas, Juan Manuel
Abstract: Archaeological remains have highlighted the fact that the interglacial Marine Isotope Stage (MIS) 11 was a threshold from the perspective of hominin evolution in Europe. After the MIS 12 glaciation, considered one of the major climate-driven crises experienced by hominins, the archaeological records show an increasing number of occupations, evidence of new subsistence behaviors, and significant technical innovations. Here, we used statistical and geographic techniques to analyze the amphibian- and reptile-based paleoclimate and habitat reconstructions generated from a large data set of the Iberian Peninsula to (1) investigate if temperature, precipitation, and/or forest cover may have impacted the hominin occupation of the territory during the Early and Middle Pleistocene, (2) propose an 'Iberian' ecological model before and after the MIS 12/11 transition, and (3) evaluate, based on this model, the potential hominin occupation at a European scale. The results indicate the existence of climatic constraints on human settlement related to rainfall and environmental humidity. The Early Pleistocene and the first half of the Middle Pleistocene are dominated by the occupation of relatively humid wooded areas, whereas during the second part of the Middle Pleistocene, a broadening of the earlier ecological niche is clearly observed toward the occupation of more open arid areas. Based on the estimated occupational niche for hominins, a maximum potential distribution for early hominins is proposed in Europe before and after 426 ka. Results also indicate that parts of the Iberian Peninsula may not have been suitable for early hominin occupation. Our ecological model is consistent with the pattern of hominin occupation observed in northern and central Europe, where the earliest evidence reflects only pioneering populations merely extending their ranges in response to the expansion of their preferred habitats, as compared with a more sustained occupation by 400 ka. Highlights: Human settlement in southern Europe is related to rainfall and environmental humidity. Before MIS 11, hominins occupied relatively humid wooded areas. After MIS 11, hominins had the potential to be in more open arid environments. The potential distribution for early hominins after 426 ka is much larger in Europe. Mediterranean Europe was not always a suitable place for early hominins.